On Possibility of Controlling of Temperature of Gases and Liquids in a Transportation System by Local Cooling or Heating - L. Pankratov, (Indian Journal of Advanced Mathematics (IJAM), 2025)
In this paper we consider an approach of changing the temperature of liquids and gases in the pipeline by local heating and cooling. We introduce a model of heat transfer with account forced convection. Also we introduce an analytical approach for prognosis of heat transfer.